PENGARUH KEPUASAN KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI (Studi Kasus Pada Pegawai Biro SDM Kementerian Keuangan Republik Indonesia) - Nurulita Rusdiningrum (2022)
The research was carried out with the purpose of knowing and proving whether there was an effect on Job Satisfaction, Work Discipline and Work Environment on the Employee Performance in Human Resources Bureau of the Ministry of Finance, with total sample 60 employees. The number of the employees is obtained by using the Probability Sampling technique and Simple Random Sampling by spin-wheels. SmartPLS3.0 application is used as the test equipment in processing the research data using the Partial Test (T test) and Simultaneous Test (F Test). The result obtained from this study are (1) there is an effect or positive and significant influence of Job satisfaction on the Employee performance of Human Resources Bureau of the Ministry of Finance. (2) there is an effect or positive and significant influence of Work Discipline on the Employee performance of Human Resources Bureau of the Ministry of Finance. (3) there is an effect or positive and significant influence of Work Environment on the Employee performance of Human Resources Bureau of the Ministry of Finance. (4) there is an influence on the Employee performance of the Human Resources Bureau of the Ministry of Finanve simultaneously.